INGAP-PP up-regulates the expression of genes and proteins related to K-ATP(+) channels and ameliorates Ca2+ handling in cultured adult rat islets - Silva, Kelly E.; Barbosa, Helena C.; Rafacho, Alex; Bosqueiro, Jose R. [UNESP]; Stoppiglia, Luiz F.; Carneiro, Everardo M.; Borelli, Maria I.; Del Zotto, Hector; Gagliardino, Juan J.; Boschero, Antonio C. (Elsevier B.V., 2008)
Islet Neogenesis Associated Protein (INGAP) increases pancreatic beta-cell mass and potentiates glucose-induced insulin secretion. Here, we investigated the effects of the pentadecapeptide INGAP-PP in adult cultured rat islets upon the expression of proteins constitutive of the K-ATP(+) channel, Ca2+ handling, and insulin secretion. The islets were cultured in RPMI medium with or without INGAP-PP for four days. Thereafter, gene (RT-PCR) and protein expression (Western blotting) of Foxa2, SUR1 and Kir6.2, cytoplasmic Ca2+ ([Ca2+](i)), static and dynamic insulin secretion, and Rb-86 efflux were measured. INGAP-PP increased the expression levels of Kir6.2, SUR1 and Foxa2 genes, and SUR1 and Foxa2 proteins. INGAP-PP cultured islets released significantly more insulin in response to 40 mM KCl and 100 mu M tolbutamide. INGAP-PP shifted to the left the dose-response curve of insulin secretion to increasing concentrations of glucose (EC50 of 10.0 +/- 0.4 vs. 13.7 +/- 1.5 mM glucose of the controls). It also increased the first phase of insulin secretion elicited by either 22.2 mM glucose or 100 mu M tolbutamide and accelerated the velocity of glucose-induced reduction of Rb-86 efflux in perifused islets. These effects were accompanied by a significant increase in [Ca2+](i) and the maintenance of a considerable degree of [Ca2+](i) oscillations. These results confirm that the enhancing effect of INGAP-PP upon insulin release, elicited by different secretagogues, is due to an improvement of the secretory function in cultured islets. Such improvement is due, at least partly, to an increased K-ATP(+) channel protein expression and/or changing in the kinetic properties of these channels and augmented [Ca2+](i) response. Accordingly, INGAP-PP could potentially be used to maintain the functional integrity of cultured islets and eventually, for the prevention and treatment of diabetes. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: cytoplasmic Ca2+; cultured pancreatic islets; Foxa2; insulin secretion; INGAP-PP; K-ATP(+) channels; Kir6.2; SUR1